Screening of oral premalignant lesions in smokers using toluidine blue - Yanti Leosari; Sri Hadiati; Dewi Agustina (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: A smoker is associated with the risk of developing oral premalignant lesions due to the cacinogenic contents in cigarette. Toluidine blue is a basic chromatic dye used in screening the presence of premalignant lesions due to its ability to detect acidic components in cells and tissues. Purpose: This study was purposed to observe the outcomes of toluidine blue staining on oral mucosa of smokers and non smokers and to find out whether quantity and duration of smoking affect the final results of toluidine blue staining. Methods: Forty male subjects, aged 20-60 years old were involved in this study, consisted of 10 heavy smokers, 10 moderate smokers, 10 light smokers and 10 non smokers. Subjects were instructed to rinse their mouths with mineral water for 20 seconds followed by acetic acid 1% for another 20 seconds. Toluidine blue stain was applied in excess and left on site for 1 minute. Subjects were instructed to rinse with acetic acid 1% and sufficient water consecutively for 20 seconds each. The areas of oral mucosa that stained blue were captured with intraoral camera and transferred to the computer unit. The staining procedure was repeated after 14 days. Results: Chi-square test showed that toluidine blue positive staining dominates the smokers group. Regression and correlation test indicate that Toluidine blue staining is more obvious in subjects who consume more cigarettes. Conclusion: It was concluded that oral mucosa of smokers absorbed more toluidine blue than that of non smokers and retention of toluidine blue is affected by quantity and duration of smoking.